Men as cultural ideals cultural values moderate gender stereotype content. [article]. - Cuddy, Amy J. C.; Wolf, Elizabeth B.; Glick, Peter; Crotty, Susan; Chong, Jihye; Norton, Michael I.
Four studies tested whether cultural values moderate the content of gender stereotypes, such that male stereotypes more closely align with core cultural values (specifically, individualism vs. collectivism) than do female stereotypes. In Studies 1 and 2, using different measures, Americans rated men as less collectivistic than women, whereas Koreans rated men as more collectivistic than women. In Study 3, bicultural Korean Americans who completed a survey in English about American targets rated men as less collectivistic than women, whereas those who completed the survey in Korean about Korean targets did not, demonstrating how cultural frames influence gender stereotype content. Study 4 established generalizability by reanalyzing Williams and Best's (1990) cross-national gender stereotype data across 26 nations. National individualism-collectivism scores predicted viewing collectivistic traits as more-and individualistic traits as less-stereotypically masculine. Taken together, these data offer support for the cultural moderation of gender stereotypes hypothesis, qualifying past conclusions about the universality of gender stereotype content. -- (from the authors)
Keywords: Gender stereotypes-Periodicals.; Stereotype content-Periodicals.; Culture-Periodicals.